Bacteriological Etiology of Flood Affected Diarrhoeal Patients Admitted in Dhaka Medical College Hospital and Antibiogram of the isolates (Bangladesh Journal of Medical Microbiology, 2016)
Diarrhoea is a self-limiting  disease  caused by various  enteropathogens and antimicrobial  therapy  is  an  important adjunct  to  fluid  therapy  in  the  management of the  cases.  We have studied  the  flood-affected  diarrhoeal  (post-flood diarrhoea) patients  admitted in  Dhaka Medical College Hospital  during  August to September,  2007.  A total  of ll4 faecal  samples  were  collected  from  the  patients of all age  groups,  and  investigated  for  bacterial  enteropathogens. Specimens  were cultured  in  appropriate  media and  identification  of the  organisms  showing  growth  was done  by relevant  biochemical  tests.  In addition, the isolates of Vbrio cholera wer confirmed  using  pollvalent  antisera. Sensitivity of the isolated organisms was done by disc diffusion method.  Among the isolated bacterial enteropathogens, majority was V. cholera (46, 40.3%). Other  isolates  included Escherichia coli (18,  23.0%),  Aeromonas species  (8,10.O%)  and V parahaemolyticus  (5,  7.0%). No pathogenic bacteria were isolated from 27 of the cases.  No Salmonella or Shigella was detected in any case. Majority of the cases  (24, 52.0%)  infected  with V cholerae  were  children  having  less than  L0 years of  age. Most of the isolates of V cholerae (77.7%) were sensitive to Ciprofloxacin.  Almost all of the V cholerae isolates (97.90 ) were resistant to Tetracycline, followed by Co-trimoxazloe (93,5%)  and  Nalidixic  acid (59.2%).  All of the E. coli isolates (100.0%) were sensitive to Ceftriaxone, followed by Ceftazidime (88.8%) and Ciprofloxacin (77.7oh).  Thus it  can  be concluded  that  Ciprofloxacin and Ceftriaxone  can  be considered  as the drugs  ofchoice  for  the  treatment  of  post-flood  diarrhoea  along  with proper  rehydration  therapy.Bangladesh  J Med Microbiol2008;  02 (01):13-17DOI: http://dx.doi.org/10.3329/bjmm.v8i1.21929